Prognostic significance of Kadish staging in esthesioneuroblastoma: An analysis of the National Cancer Database. Issue 10 (17th August 2017) - Konuthula, Neeraja; Iloreta, Alfred M.; Miles, Brett; Rhome, Ryan; Ozbek, Umut; Genden, Eric M.; Posner, Marshall; Misiukiewicz, Krzysztof; Govindaraj, Satish; Shrivastava, Raj; Gupta, Vishal; Bakst, Richard L.
Abstract: Background: Given the rarity of esthesioneuroblastoma, it is difficult to validate a staging system. The purpose of this study was to investigate the utility of the Kadish staging system in esthesioneuroblastoma using the National Cancer Database (NCDB). Methods: One thousand one hundred sixty‐seven patients with esthesioneuroblastoma were identified from the NCDB. Results: Five‐year survival was 80.0% for Kadish A, 87.7% for Kadish B, 77.0% for Kadish C, and 49.5% for Kadish D. Kadish B had higher survival than Kadish A. More Kadish B patients received surgery with adjuvant therapy than Kadish A patients (41.6% vs 32.5%; P = .0038) and also had more positive margins (21.6% vs 11.3%; P = .03). There was no difference in age distribution, sex, race, or neck dissection status between the 2 groups. Conclusion: Kadish B had greater survival than Kadish A, but the treatment characteristics could not account for this difference. The utility of early‐stage Kadish staging is uncertain and requires further study.